2009
DOI: 10.1007/s00228-009-0622-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pharmacokinetic profile of levodopa throughout the day between levodopa/carbidopa/entacapone and levodopa/carbidopa when administered four or five times daily

Abstract: Objectives To compare plasma levodopa concentrations after repeated doses of levodopa/carbidopa/entacapone (LCE) and levodopa/carbidopa (LC). Methods Open-label, randomized, two-period, activecontrolled, cross-over study with four dosing regimens: groups I and II (healthy volunteers and Parkinson's disease patients) received levodopa 100 mg or 150 mg four times daily, respectively, and groups III and IV (healthy volunteers) received the same strengths of levodopa five times daily. Pharmacokinetic (PK) paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 25 publications
2
37
1
1
Order By: Relevance
“…But this trial also shows a general tendency of homocysteine accumulation during repeated acute oral levodopa/DDI administration with and without EN over the threshold of 15 μmol/l within 2 days (Muller and Muhlack 2010). Expectedly, there was a general increase of levodopa plasma occurrence with additional EN application (Kuoppamaki et al 2009). Earlier investigations showed that less-pronounced troughs and higher C max of levodopa concentrations appear after addition of EN to levodopa/DDI Kuoppamaki et al 2009).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…But this trial also shows a general tendency of homocysteine accumulation during repeated acute oral levodopa/DDI administration with and without EN over the threshold of 15 μmol/l within 2 days (Muller and Muhlack 2010). Expectedly, there was a general increase of levodopa plasma occurrence with additional EN application (Kuoppamaki et al 2009). Earlier investigations showed that less-pronounced troughs and higher C max of levodopa concentrations appear after addition of EN to levodopa/DDI Kuoppamaki et al 2009).…”
Section: Discussionmentioning
confidence: 91%
“…Expectedly, there was a general increase of levodopa plasma occurrence with additional EN application (Kuoppamaki et al 2009). Earlier investigations showed that less-pronounced troughs and higher C max of levodopa concentrations appear after addition of EN to levodopa/DDI Kuoppamaki et al 2009). We confirm that T max further goes up with EN supplementation in PD patients .…”
Section: Discussionmentioning
confidence: 95%
“…Currently available PD medications often result in significant variations in plasma levodopa levels (40)(41)(42), which may contribute to the motor fluctuations observed in advanced disease (43). Stable plasma levodopa concentrations during LCIG administration may result in more consistent dopaminergic stimulation in the brains of PD patients and subsequent improvement in clinical symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…Проводимые в Центре экстрапирамидных заболе-ваний нервной системы открытое рандомизированное перекрестное исследование, посвященное изучению фармакокинетики однократной дозы леводопа / карби-допа / энтакапон 200 и леводопа / карбидопа контроли-руемого высвобождения 200, а также изучение эффек-тивности леводопа / карбидопа / энтакапон коррекции ночных симптомов БП при приеме однократной дозы перед сном показали статистически значимое сниже-ние выраженности симптомов БП, проявляющихся в ночное время [9][10][11][12].…”
Section: Discussionunclassified